Fused Filament Fabrication of Actuating Objects. Issue 10 (21st July 2022) - Chalissery, Dilip; Schönfeld, Dennis; Walter, Mario; Ziervogel, Fabian; Pretsch, Thorsten
Abstract: Thermoresponsive objects can be manufactured from shape memory polymers (SMPs) via fused filament fabrication (FFF). Here a new technological approach to obtain thermally actuating objects using an in‐house synthesized, phase segregated poly(ester urethane) (PEU) is introduced. Under almost stress‐free conditions of a dynamic mechanical analysis, cuboid objects obtained from FFF shrank when heated to 62 °C and expanded when cooled to 15 °C with a maximum thermoreversible strain of 7.2%. Actuation can be traced back to the phenomena of melting‐induced contraction and crystallization‐induced elongation of the PEU's soft segment, supported by internal stresses as implemented in course of FFF. To translate small changes in shape to a next larger scale, an artificial butterfly is developed in which the movements of two actuator elements are transferred to the wings with the aid of a lever concept. Following a different approach, additive manufacturing of cylindrical samples implied application potential as a self‐sufficient gripper, enabling a programmable material behavior in the sense of temperature‐controlled gripping, transport, and release of exemplarily selected smooth surfaced objects in the form of vials. Abstract : Commonly, shape memory polymers require a thermomechanical treatment to become thermoresponsive. Here, the additive manufacturing method "fused filament fabrication" is used to build objects with thermally bistable states from an in‐house synthesized poly(ester urethane). Furthermore, ways are shown how to harness the actuation. The introduced platform technology facilitates the production of new generations of programmable materials.